URGENSI KECERDASAN EMOSIONAL Urgensi Kecerdasan Emosional Kepala Sekolah Dalam Meningkatkan Motivasi Kinerja Guru (Studi Kasus Playgroup Budi Mulia Dua Terban Yogyakarta) - Choirul Hidayah Choirul Hidayah (Universitas Nahdlatul Ulama Blitar, 2022)
There is still a lack of understanding related to the emotional intelligence of school principals in the world of education in leading their members. The low emotional intelligence of leadership in the principal will have an impact on its members. The impact on its members includes the frequent occurrence of social jealousy and decreased work motivation caused by the lack of attention and concern of a leader to his members. In the world of education, it is important to have a leader or school principal who has emotional intelligence to strengthen brotherhood within the institution and foster motivation at work. This is what underlies this research, this study aims to find out about (1) knowing and understanding the leadership style of the principal used in the Budi MuliaDuaTaban Playgroup Yogyakarta (2) to find out the importance of a school principal having emotional intelligence for teachers in the Budi Mulia Playgroup DuaTerban Yogyakarta (3) to find out the principal's efforts in increasing the work spirit of teachers in the Budi MuliaDuaTerban Playgroup Yogyakarta A qualitative approach with descriptive analysis method is used in this study to answer the problem. The subjects in this study included school principals and teachers at the Budi MuliaDuaTerban Playgroup Yogyakarta with the criteria of having taught at least 3 years. Data collection in this study was carried out by interview, observation and documentation methods. The data that has been collected is then analyzed using descriptive analytical techniques. The research carried out shows that the results of the study are (1) the leadership style of the principal at the Playgroup Budi MuliaDuaTerban Yogyakarta is a combination of authoritarian, democratic, laizze Freire, and kurakura. (2) the importance of principals having emotional intelligence attitudes for teachers, namely to provide a comfortable and safe feeling at work, create a pleasant working atmosphere, make it easier to communicate with each other and overcome work conflicts in the work environment. (3) there are several things that principals do to increase motivation at work, one of which is facilities.